Marketing social corporativo nas indústrias do Paraná - Oliveira, Rosemeri Schneider de (2006)
The Corporate Social Marketing has been a phenomenon gradually more and more observed in Brazilian companies. That has been happening partly due to the current context of Brazilian society, as well as partly justified by movements that happen in a global scale, as it can be observed in the reduction of participation of National States in economy. Moreover, it is a phenomenon that can be explained by the reformulation and adaptation of the marketing administrative processes, implemented by the companies in their own sphere of action. Taking the assumptions above into consideration, some questions emerge, becoming an invitation to a reflection regarding of the Corporate Social Marketing: ' Which are the practices' and 'How do the practices of corporate social marketing, being developed by the big and large-scale industries of the State of Paraná happen? Aiming at characterizing those practices, a research, of descriptive nature, was accomplished in the large-scale industries located in the State. Such industries were classified, starting from data base from 'Federação das Indústrias do Estado do Paraná' (FIEP), and following criteria established by SEBRAE, as industries possessing a personal staff around five hundred or more employees. The research was performed in different stages. The first stage comprised, in which an inquiry was applied by phoning all managers involved in the programs of corporate social action of large-scale industries of Paraná, which are members or are engaged to the Federation of the Industries system named 'Federação das Indústrias do Estado do Paraná (FIEP) In the second phase, the instrument of data collection used was a structured questionnaire using electronic mail as a strategy of sending and monitoring messages and responses. Such instrument resulted in a total response equivalent to 84,10%, concerning e- mail return. Data tabulation was carried out by using Le Sphinx Plus statistical package. The main results concerning the study showed that the accomplishment of the Corporate Social Marketing in Paraná industries is a relatively new phenomenon, occurring in the last twelve years. Thus, its practice is still in assimilation, and that is directly linked to the existence of entities that are partners and provide credibility to the industries. It was observed that, its accomplishment focus the region, concentrating itself in the area of education, once the children are the main beneficiaries. As a result, it was observed that the Corporate Social Marketing has been leading, more to a great improvement regarding both, the relationship of the industries with their stakeholders and regarding their own corporate images, than to an increase in terms of market share or participation in the market.